Virtual Screening of Natural Compounds for HIV 1 Reverse Transcriptase Inhibitor as Potential Drugâs Candidate - Fadilah, Rizka Elan; Fauzi, Ahmad; Widiansyah, Arindra Trisna; Wijayanti, Erna (Proceeding International Conference on Global Resource Conservation, 2015)
AIDS is one of mayor health problem in the world, commonly caused by Human Immunodeficiancy virus 1 (HIV-1).Â  Reverse transcriptase is the target of the most widely used treatments for AIDS. One of the problem from treatments is drug resistant. This research aim to discover a new potential drugâs candidate from natural compound to inhibit activity of HIV 1 Reverse Transcriptase. Top ten compounds from Specs Natural Products database as the result of virtual screening by MTIOpenScreen are docked and analyzed using Pyrx 0.8 software. Based on analysis and visualization of 2D and 3D sructure using LigPlus and PyMol softwares, known that ZINC57657 (-8 Kcal/mol)and common drug against HIV 1 Reverse Transcriptase, Lamivudine (-5,6 Kcal/mol) equally capable to bind in several amino acids (Thr 131 and Gln 23) located in the active site of HIV 1 Reverse Transcriptase.Keywords: Drugâs candidate; HIV 1 reverse transcriptase; natural compounds; virtual screening